Epidemiology of Pediatric Deaths in 2017 Kermanshah Earthquake - Alireza Khatony; Fatemeh Janatolmakan; Bahar Andaieshgar; Maryam Janatolmakan (Mazandaran University of Medical Sciences, 2019)
Background: Children, as a vulnerable population in society, are at greater risk of injury compared to others. One of the unpredictable events causing death every year in the world is earthquake. This study aimed at investigating the epidemiology of pediatric deaths in 2017 Kermanshah Earthquake.  Methods: Adopting a descriptive method, the present study was conducted in Imam Reza Hospital located in Kermanshah, Iran after earthquake occurred in this city in 2017. The study population consisted of all children aged <18 years who were referred to this hospital due to the injuries caused by the earthquake. data were collected from the resources available at the hospital and the referral server.  Results: From among 60 children referred to the hospital, 5 (8.33%) had died (Mean±SD age, 37.06±34.19 months; 3 boys and 2 girls); 3 (60%) were living in urban areas and 2 (40%) in rural area; 2(40%) were diagnosed with multi-trauma, 2 (40%) with infectious diseases, and 1 (20%) with pneumonia; 1 (20%) had head and limb injuries, and 1 (20%) abdominal and limb injuries. All of the dead children had Glasgow Coma Score (GCS)<15, two of whom had GCS<10. The hospitalization for 40% of patients (n=2) lasted for one day and for 60% of them (n=3) its period was less than 10 days. Conclusions: It seems that using previous managerial experiences is inevitably necessary to reduce injuries to individuals, especially children, in the possible upcoming disasters.